SCIENTIFICAL METHOD OF THE TAFSIR OF PESANTREN: A STUDY OF KYAI BISRI MUSTAFA’S TAFSIR SURAH YASIN (1915-1977) - Islah Gusmian; Mustaffa Abdullah (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2022)
Studies on the history of Qur'anic interpretation (tafsir) in Indonesia, such as those conducted by Riddel, A.H. John, and Howard M. Federspiel, generally do not relate to the tradition and culture of pesantren. In fact, as the oldest Islamic educational institution in Indonesia, pesantren has a dynamic and complex history and tradition of Qur'anic interpretation literacy. This article examines one side of the tradition of Qur'anic interpretation in pesantren through Tafsir Surah Yasinby Kyai Bisri Mustafa. This book of tafsir was selected; in addition to representing the tradition of interpretation in pesantren, science is used to explain the messages of the Qur'an in it. In this book, the explanation of science is not used as a justification for the scientificity of the Qur'an, nor is it used as a way to Islamise science, but as an affirmation of the spiritual aspects and implicit messages of the Qur'anic text. Axiologically, Kyai Bisri uses the scientific approach, not for science but to explain the sunnatullah (natural law) and divine existence. Through Tafsir Surah Yasin, he rejects Western science that tends to be materialistic-nihilistic and, at the same time, affirms the transcendence of science in Islam.